Comparison of simulated and observed trapped and precipitating electron fluxes during a magnetic storm. Issue 20 (29th October 2015) - Chen, Margaret W.; Lemon, Colby L.; Orlova, Ksenia; Shprits, Yuri; Hecht, James; Walterscheid, R. L.
Abstract: The ability to accurately model precipitating electron distributions is crucial for understanding magnetosphere‐ionosphere‐thermosphere coupling processes. We use the magnetically and electrically self‐consistent Rice Convection Model‐Equilibrium (RCM‐E) of the inner magnetosphere to assess how well different electron loss models can account for observed electron fluxes during the large 10 August 2000 magnetic storm. The strong pitch angle scattering rate produces excessive loss on the morning and dayside at geosynchronous orbit (GEO) compared to what is observed by a Los Alamos National Laboratory satellite. RCM‐E simulations with parameterized scattering due to whistler chorus outside the plasmasphere and hiss inside the plasmasphere are able to account simultaneously for trapped electron fluxes at 1.2 keV to ~100 keV observed at GEO and for precipitating electron fluxes and electron characteristic energies in the ionosphere at 833 km measured by the NOAA 15 satellite. Key Points: Strong scattering produces excessive loss on the morning and dayside Parameterized scattering due to waves accounts for electron fluxes at GEO Parameterized loss model consistent with observed precipitating electron fluxes